A new genus and species of cixiid planthopper (Hemiptera: Delphacoidea: Cixiidae) from Belize, including a key to the American Pentastirini and a checklist of Belizean Fulgoromorpha - Hendrix, Solomon V.; Bartlett, Charles R. (Zootaxa, 2025)
Pictoliarus gen. nov. is described for the distinctive species P. zoetropeus sp. nov. from Belize as part of an ongoing review of the Pentastirini (Hemiptera: Cixiidae) of the Americas. A key to the genera represented in North and South America is presented. A compiled listing of the planthopper fauna of Belize includes 104 taxa (including new records for 31 species and one subspecies). The findings underscore the existence of a rich, but understudied planthopper fauna in Belize.